THE INFLUENCE OF PRICE AND PRODUCT VARIETY ON IMPULSE BUYING THROUGH POSITIVE EMOTION AMONG GENERATION Z CONSUMERS OF SCARLETT PERFUME ON TIKTOK SHOP - Muhimmatur Rodhiyah (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the effect of price and product variety on impulse buying through positive emotion among Generation Z consumers of Scarlett perfume on TikTok Shop. This study employed a quantitative approach using an explanatory research method. A total of 150 respondents were selected through purposive sampling. Data were collected using an online questionnaire distributed via Google Forms and analyzed using the Partial Least Square (PLS) method. The results indicate that price has a positive and significant effect on impulse buying, whereas product variety has no significant effect on impulse buying. In addition, price and product variety have positive and significant effects on positive emotion, which also positively and significantly influences impulse buying. Furthermore, positive emotion mediates the relationship between price and impulse buying, as well as between product variety and impulse buying among Generation Z consumers of Scarlett perfume on TikTok Shop. This study is expected to contribute to the marketing literature, particularly regarding impulse buying behavior among Generation Z in the digital era, and to provide practical insights for businesses in developing pricing strategies and product variety to enhance consumers' positive emotions and encourage impulse buying.